Conformational IgE epitopes of peanut allergens Ara h 2 and Ara h 6. Issue 8 (27th June 2016) - Chen, X.; Negi, S. S.; Liao, S.; Gao, V.; Braun, W.; Dreskin, S. C.
Summary: Background: Cross‐linking of IgE antibody by specific epitopes on the surface of mast cells is a prerequisite for triggering symptoms of peanut allergy. IgE epitopes are frequently categorized as linear or conformational epitopes. Although linear IgE‐binding epitopes of peanut allergens have been defined, little is known about conformational IgE‐binding epitopes. Objective: To identify clinically relevant conformational IgE epitopes of the two most important peanut allergens, Ara h 2 and Ara h 6, using phage peptide library. Methods: A phage 12mer peptide library was screened with allergen‐specific IgE from 4 peanut‐allergic patients. Binding of the mimotopes to IgE from a total of 29 peanut‐allergic subjects was measured by ELISA. The mimotope sequences were mapped on the surface areas of Ara h 2 and Ara h 6 using EpiSearch. Results: Forty‐one individual mimotopes were identified that specifically bind anti‐ Ara h 2/Ara h 6 IgE as well as rabbit anti‐Ara h 2 and anti‐Ara h 6 IgG. Sequence alignment showed that none of the mimotope sequences match a linear segment of the Ara h 2 or Ara h 6 sequences. EpiSearch analysis showed that all the mimotopes mapped to surface patches of Ara h 2 and Ara h 6. Eight of the mimotopes were recognized by more than 90% of the patients, suggesting immunodominance. Each patient had distinct IgE recognition patterns but the recognition frequency was not correlated to the concentration of peanut specific IgE or to clinical history. Conclusions: The mimotopes identified in this study represent conformational epitopes. Identification of similar surface patches on Ara h 2 and Ara h 6 further underscores the similarities between these two potent allergens.